Vegetation history, climate and human impact over the last 15,000 years at Lago dell’Accesa (Tuscany, Central Italy) - Drescher-Schneider, Ruth; de Beaulieu, Jacques-Louis; Magny, Michel; Walter-Simonnet, Anne-Véronique; Bossuet, Gilles; Millet, Laurent; Brugiapaglia, Elisabetta; Drescher, Anton (Vegetation History and Archaeobotany, 2007)
Interdisciplinary studies of the sediments of Lago dell’Accesa started in 2001. We present here results from the palynological study. The pollen diagram provides a record of vegetation and climatic change spanning over 15,000 years. The oldest pollen spectra show a late-glacial steppe vegetation typical of central and southern Italy during this period. The Late-glacial Interstadial, interrupted by two cooling events, is dominated by open deciduous oak forests. The Younger Dryas is represented by 150 cm of sediment and shows the presence of steppic vegetation. The Holocene vegetation is characterised by alternating dominance of deciduous oaks and Quercus ilex. The three zones characterised by Q. ilex are accompanied by peat layers marking lake-level lowering at ca. 8600–7900, 4600–4300 and 3700–2800 cal b.p. Between approximately 9000 and 6000 cal b.p. extensive Abies-forests existed on the Colline Metallifere located 15–20 km to the north and northeast of the lake. Local ﬁr populations may also have existed by the lake. Human impact starts at approximately 8000 cal b.p. during the Neolithic period, and increases at ca. 4300 cal b.p. Castanea and Juglans pollen is recorded from ca. 2800 cal b.p. The impact of the Etruscan settlement near the lakeshore is shown in the increasing values of arable crops, species of secondary forest canopy (Ericaceae, Pinus, Pistacia, Myrtus) and anthropogenic indicators (Chenopodiaceae, Plantago lanceolata, Rumex etc).
Keywords: Abies; Central Italy; Holocene; human impact; Late Pleistocene; Mediterranean vegetation; Pollen analysis